2013
DOI: 10.1055/s-0032-1328291
|View full text |Cite
|
Sign up to set email alerts
|

Mammographic Density and Prediction of Nodal Status in Breast Cancer Patients

Abstract: !Aim: Nodal status remains one of the most important prognostic factors in breast cancer. The cellular and molecular reasons for the spread of tumor cells to the lymph nodes are not well understood and there are only few predictors in addition to tumor size and multifocality that give an insight into additional mechanisms of lymphatic spread. Aim of our study was therefore to investigate whether breast characteristics such as mammographic density (MD) add to the predictive value of the presence of lymph node m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…In this material we observed that decreasing radiologic tumor size was associated with N0 status. Pathological tumor size is a strong predictor for SLN status and often included in prediction models, although it is a postoperative variable [10,19,20]. These and previous results indicate that mammographic tumor size could replace pathological tumor size assessed from the surgical specimen as a predictor for N0 status.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…In this material we observed that decreasing radiologic tumor size was associated with N0 status. Pathological tumor size is a strong predictor for SLN status and often included in prediction models, although it is a postoperative variable [10,19,20]. These and previous results indicate that mammographic tumor size could replace pathological tumor size assessed from the surgical specimen as a predictor for N0 status.…”
Section: Discussionmentioning
confidence: 62%
“…Yang et al [21] created a prediction model for ALN status using a radiomic signature on mammography (n=147) and with an AUC of 0.88 in the validation cohort, indicating a promising predictive capacity of mammographic features for N0 status. A study by Hack et al [20] evaluated mammographic density and postoperative clinicopathological variables for prediction of N0 status. No association was discovered between mammographic density and SLN status, similar to our ndings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The following methodology was used in several previous works [ 4 , 6 , 7 , 10 , 13 , 30 , 31 , 45 , 47 50 ]. Quantitative computer-based threshold density assessments were carried out by two different readers.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies have reported that MD affects the prognosis of BC patients [16,17], and MD has been found to correlate with tumor proliferation in several subgroups [18,19]. However other studies did not show a correlation between MD and Prognosis [20e23] and further no association was found between MD and lymph node metastases [24].…”
Section: Introductionmentioning
confidence: 99%